Analysis of the equity of emergency medical services: a cross-sectional survey in Chongqing city. Issue 1 (December 2015) - Liu, Yalan; Jiang, Yi; Tang, Shenglan; Qiu, Jingfu; Zhong, Xiaoni; Wang, Yang
Abstract Background Due to reform of the economic system and the even distribution of available wealth, emergency medical services (EMS) experienced greater risks in equity. This study aimed to assess the equity of EMS needs, utilisation, and distribution of related resources, and to provide evidence for policy-makers to improve such services in Chongqing city, China. Methods Five emergency needs variables (mortality rate of maternal, neonatal, cerebrovascular, cardiovascular, injury and poisoning) from the death surveillance, and two utilisation variables (emergency room visits and rate of utilisation) were collected from Chongqing Health Statistical Year Book 2008 to 2012. We used a concentration index (CI) to assess equality in the distribution of needs and utilisation among three areas with different per-head gross domestic product (GDP). In each area, we randomly chose two districts as sample areas and selected all the medical institutions with emergency services as subjects. We used the Gini coefficient (G) to measure equity in population and geographic distribution of facilities and human resources related EMS. Results Maternal-caused (CI: range −0.213 to −0.096) and neonatal-caused (CI: range −0.161 to −0.046)deaths declined in 2008–12, which focusing mainly on the less developed area. The maternal deaths were less equitably distributed than neonatal, and the gaps between areas gradually become more noticeable. For cerebrovascular (CI: range 0.106 to 0.455), cardiovascular (CI: range 0.101 to 0.329), injury and poisoning (CI: range 0.001 to 0.301) deaths, we documented a steady improvement of mortality; the overall equity of these mortalities was lower than those of maternal and neonatal mortalities, but distinct decreases were seen over time. The patients in developed area were more likely to use EMS (CI: range 0.296 to 0.423) than those in less developed area, and the CI increased over the 5-year period, suggesting that gaps in equity were increasing. The population distribution of facilities, physicians and nurses (G: range 0.2 to 0.3) was relatively equitable; the geographic distribution (G: range 0.4 to 0.5) showed a big gap between areas. Conclusions In Chongqing city, equity of needs, utilization, and resources allocation of EMS is low, and the provision of such services has not met the needs of patients. To narrow the gap of equity, improvement in the capability of EMS to decrease cerebrovascular, cardiovascular, injury and poisoning cases, should be regarded as a top priority. In poor areas, allocation of facilities and human resources needs to be improved, and the economy should also be enhanced.